Komunikacijski model književne vzgoje - Kordigel Aberšek, Metka (Jezik in slovstvo, 1999)
A communicative model of literary education is presented that was used in the new primary school curriculum. It is based on three sciences, which - each within its own framework - explore elements of the communicative situation in the classroom in which the reader and the literary text meet, in the presence of the teacher as the organiser or the manager of the learning situation. The model borrows its knowledge about the student and his receptive ability from the young reader studies, its knowledge about the literary work from literary studies, and its knowledge about what happens when the reader and the literary text meet from aesthetics of reception. Following the ideas of aesthetics of reception, the communicative model of literary education presumes there exists nothing that might be termed "the real meaning of a literary text", no precious value that the author has hidden among the words of his literary creation and that should be found - or possibly missed - by readers in the process of reception. The meaning of a literary text is created in each reading anew as a product of interaction between the text and its reception by the reader. Within this framework, the model primarily prepares students for dialogue with a literary text and for constructing their individual meanings of texts, because it is only the student himself or herself that can make (or not make) a literary text speak to him/ her, i.e. actualise a literary text's potential meaning into his/ her own, bringing into the referential framework of literary data to be used in reception his/ her own specific expectations that belong to his developmental and biographically determined field of interests, desires, needs and experiences, in other words, to his horizon of expectations. A reader can understand a literary text only to the extent matching the ability of his horizon of expectation to receive signals or data for reception conveyed by a literary text. Using principles of aesthetics of reception, literary theory and studies on development of literary reading, the communicative model of literary education guides the young reader systematically, step by step from spontaneous to reflexive reception of a literary text, i.e. to a developed ability of literary reading. In this process, the model does not focus on increasing the number of textual signals perceived by the reader, but primarily on a systematic development of his/ her ability to understand and evaluate these signals. This is the principle of Less may be more, with special attention going to the selection of textual signals brought to students' attention by the teacher. The teacher selects only those signals that students are capable of registering, understanding and evaluating within their horizon of expectation as defined by their ability to receive literature and their stage of development at a given point in time. The basic novelty of the communicative model of literary education is its attempt to define the structural complex of receptive ability and its description of the child's (literary) reading (=receptive) dvelopment within each of its structural component. Doing this, the communicative model of literary education manages to break down the contiguous progression from the so-called spontaneous to the so-called reflective reception into a manageable number of partial objectives that the teacher may seek to pursue in his/her didactic communication
Keywords: književna vzgoja; komunikacija; recepcija; didactic method; didaktika